Fermentation profile and chemical composition of cassava root silage - PITIRINI,Juliana Schuch (2021)
ABSTRACT The use of cassava root silage for animal feeding is a suitable option for farmers who grow cassava as an alternative product and for cattle ranchers who have to deal with high prices of corn. Our objective was to determine the effects of cassava genotypes and the correction of soil acidity on the microbial population, fermentation characteristics, chemical composition, aerobic stability and losses of cassava root silage. We used a 2 × 3 factorial design in completely randomized blocks, with four replications. We evaluated two cassava genotypes (Caeté and Manteiguinha) and three methods of soil acidity correction (lime, gypsum, and lime+gypsum). The roots were harvested 11 months after planting, ensiled in PVC silos, and stored for 45 days. No interaction was observed between genotypes and soil acidity correction for any of the evaluated parameters. The silage of Caeté genotype showed the highest concentration of dry matter (421 g kg-1 fresh matter) and non-fibrous carbohydrates (893 g kg-1 dry matter), and the lowest concentrations of neutral detergent fiber (37.1 g kg-1 dry matter) . No significant differences were observed among treatments for lactic acid bacteria, yeast and mold counts in silages. Both genotypes resulted in silages with an adequate fermentation profile and considerably high aerobic stability, but with high effluent loss. The Caeté genotype showed to be potentially better for silage production due to its higher dry matter recovery. Due to the high level of effluent loss, it is recommended to test the effect of a moisture-absorbing additive during the ensiling process of these cassava roots.